2002
DOI: 10.4049/jimmunol.168.8.4025
|View full text |Cite
|
Sign up to set email alerts
|

Role of P38 Mitogen-Activated Protein Kinase Phosphorylation and Fas-Fas Ligand Interaction in Morphine-Induced Macrophage Apoptosis

Abstract: In this study, we evaluated the molecular mechanisms involved in morphine-induced macrophage apoptosis. Both morphine and TGF-β promoted P38 mitogen-activated protein kinase (MAPK) phosphorylation, and this phosphorylation was inhibited by SB 202190 as well as by SB 203580. Anti-TGF-β Ab as well as naltrexone (an opiate receptor antagonist) inhibited morphine-induced macrophage P38 MAPK phosphorylation. Anti-TGF-β Ab also attenuated morphine-induced p53 as well as inducible NO synthase expression; in contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 38 publications
(33 reference statements)
2
65
0
Order By: Relevance
“…13,17 In vitro, experiments performed on immune cells-including lymphocytes and macrophages-showed that a direct interaction with morphine resulted in up-regulation of Fas mRNA. 11,18 Together, these data assume that spleen cell sensitization to Fas-mediated apoptosis induced by opioids was a paracrine/autocrine MOR-mediated effect associated with an increase in Fas mRNA. By comparison, we investigated whether the neutralization of opioid receptor activity was associated with a lower expression of Fas mRNA in the liver.…”
Section: Resultsmentioning
confidence: 87%
“…13,17 In vitro, experiments performed on immune cells-including lymphocytes and macrophages-showed that a direct interaction with morphine resulted in up-regulation of Fas mRNA. 11,18 Together, these data assume that spleen cell sensitization to Fas-mediated apoptosis induced by opioids was a paracrine/autocrine MOR-mediated effect associated with an increase in Fas mRNA. By comparison, we investigated whether the neutralization of opioid receptor activity was associated with a lower expression of Fas mRNA in the liver.…”
Section: Resultsmentioning
confidence: 87%
“…27) The activation of p38 and JNK MAPKs in apoptosis is also linked with the induction of Fas/FasL. 49,50) Moreover, p53 can stimulate Fas transcription, and overexpressed p53 may enhance levels of Fas at the cell surface by promoting trafficking of the Fas receptor from the Golgi apparatus. 14) Therefore the activation of p38/JNK MAPK and p53 may upregulate Fas/FasL expression and then contribute to the synergistic effects of dracorhodin perchlorate with CH-11.…”
Section: Discussionmentioning
confidence: 99%
“…JNKs are among several kinases that phosphorylate p53 at Nterminal serine residues leading to a stabilization of the protein. Therefore, JNK activation might constitute a signaling pathway by which morphine causes the observed p53 phosphorylation and stabilization (Singhal et al, 2002;Tegeder et al, 2003). The effects of morphine on p53 may also be mediated through the ubiquitin ligase Mdm2 which ensures rapid p53 degradation under homeostatic conditions.…”
Section: F ␤-Arrestin As Signal Transducermentioning
confidence: 99%